The Images of the Slavic Peoples in Albert Škarvan´s Diaries from 1896 to 1926 - Korina, Natalya (Slavica, 2023)
The paper discusses the images of the Slavic peoples in Albert Škarvan’s diaries from 1896 to 1926, first published in 2019. Albert Škarvan was a Slovak intellectual of the Austro-Hungarian Empire of the late 19th and early 20th centuries, the follower of L. Tolstoy’s ideas and Christian religious philosophy. He produced philosophical reflections about the Slavic peoples of the Austro-Hungarian Empire (Slovaks, Czechs, and Serbs) in comparison with Russians and made an attempt to determine their historical mission and spiritual potential. His diaries contain many critical mentions as well as suggestions as to how to improve the situation of Slavic peoples, primarily of Slovaks, in the European dimension. This article is one of a series of papers on Albert Škarvan manuscripts.